You are on page 1of 2

# Problem 2.

3
Use section 2.3 in textbook.

## Let A be a nonsingular matrix and x, y 2 Cn . Show

Axy ⇤ A
(A 1
+ xy ⇤ ) 1
=A
1 + y ⇤ Ax
and
detA
det(A 1
+ xy ⇤ ) 1
=
1 + y ⇤ Ax
Solutions
Because the theorem, we have
(A11 A12 A221 A21 ) 1 = A111 + A111 A12 (A22 A21 A111 A12 ) 1 A21 A111 .
Assuming that A11 = A 1 , A12 = x, A221 = I, A21 = y ⇤ .

## We get the form like: (A 1 ( xIy ⇤ )) 1 =

(A 1 ) 1 + (A 1 ) 1 ( x)(I y ⇤ (A 1 ) 1 ( x)) 1 y ⇤ (A 1 ) 1
=

Axy ⇤ A
A Ax(I + y ⇤ Ax) 1 y ⇤ A, futhermore, (A 1
+ xy ⇤ ) 1
=A .
I + y ⇤ Ax
Axy ⇤ A
So Because the demostration of (A 1
+ xy ⇤ ) 1
=A
we can say
I + y ⇤ Ax
detA
our matrix have the determinant like det(A 1 + xy ⇤ ) 1 =
1 + y ⇤ Ax

4
Problem 2.4
Let A and B be compatible matrices. Show

1
B(I + AB) = (I + BA) 1 B, (I + A) 1
=I A(I + A) 1

Solutions
1
B(I + AB) = (I + BA) 1 B

## Because the theorem of matrix inverse, let A be an mxn matrix, then B is

an inverse of A i↵ AB = In and BA = In . Not that since A and In are both
nxn, B must also be an nxn matrix.
1 1
(I + A) =I A(I + A)

✓ ◆ ✓ ◆
1 0 a b
Let I = and A = , then,
0 1 c d
0 1
✓ ◆ d+1 b
a+1 b 1 @ A,
I+A = =)(I+A) 1 =
c d+1 a(d + 1) bc + d + 1
c a+1
0 1
d+1 b
1 B ⇢ ⇢ C
B C
where ⇢ = , so we have that (I+A) 1 = B C,
a(d + 1) bc + d + 1 @ c a + 1A
⇢ ⇢
0 1
bc a(d + 1) b
B ⇢ ⇢ C
B C
hence, A(I + A) = B1
B
C, futhermore
C
@ c bc d(a + 1) A
⇢ ⇢
0 1
d+1 b
B ⇢ ⇢ C
1 B C 1
I A(I + A) =B C = (I + A)
@ c a + 1A
⇢ ⇢